If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 = 1 + -8n + -4 Reorder the terms: 13 = 1 + -4 + -8n Combine like terms: 1 + -4 = -3 13 = -3 + -8n Solving 13 = -3 + -8n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '8n' to each side of the equation. 13 + 8n = -3 + -8n + 8n Combine like terms: -8n + 8n = 0 13 + 8n = -3 + 0 13 + 8n = -3 Add '-13' to each side of the equation. 13 + -13 + 8n = -3 + -13 Combine like terms: 13 + -13 = 0 0 + 8n = -3 + -13 8n = -3 + -13 Combine like terms: -3 + -13 = -16 8n = -16 Divide each side by '8'. n = -2 Simplifying n = -2
| 1/4k+3/4=5/6k-1 | | 24=24y | | -11c-35=4c-8 | | -2(4-x)=2-8 | | y=(-60)(1)+b | | 0.75p-1.25=0.333333p | | 3(x+5)=2(3x-4) | | 25=-h | | 4x+9x=292 | | n-35=25-4n | | 9(v+3)=3v-3 | | -17=-32-3/5y | | 8-8p=p | | (8a-9)(3a^2-2a-2)= | | -1/3(n+15)=6 | | 2x^2-30-12=0 | | 3u-33=-5(u+5) | | h=16t^2+12t+900 | | 3x=12.9 | | x+(3-1)=4 | | F(x)=x^3-x^2-10x-8 | | .50n-3=9 | | 16t^2+12t+900=0 | | x-3(x+4)=6x+9 | | 2*x=18 | | 60k+80=50k+100 | | -6(n+7)=4n-16 | | x-4=x-5+1 | | 3x+40x=180 | | 2*x=62 | | -2=-5w+2(w+5) | | 8X-(3X+6)=4-X |